Knowledge Translation in Job Development: Strategies for Involving Families. Issue 5 (16th November 2013) - Hall, Allison; Bose, Jennifer; Winsor, Jean; Migliore, Alberto
<x xml:space="preserve">Abstract</x> Background Although United States employment policies have increased support for people with disabilities working in community settings, the unemployment rate for this population remains very high, particularly for people with intellectual or developmental disabilities. Research shows that job developers (direct support professionals who assist people with disabilities to secure, maintain, and advance in employment) are critical to achieving quality employment outcomes. However, the extent to which job developers use practices that are considered promising in their field (such as engaging families) is not well known. Methods This brief report summarizes findings from a qualitative study about the extent to which job developers use the recommended promising practices when working with individuals and family members. Results Qualitative analysis identified the following themes among job developers: factors affecting family involvement, perceptions of family involvement, and the influence of expectation on strategies. Conclusions The field of job development faces a challenge common to many professions: translating research on best practices to those who need this knowledge the most and can use it to greatest effect. Future research should address how community rehabilitation providers (CRPs) communicate about and instill best practices, including effective family engagement, within their organizations.